Injection therapies for lateral epicondylalgia: a systematic review and Bayesian network meta-analysis. Issue 15 (21st September 2015) - Dong, Wei; Goost, Hans; Lin, Xiang-Bo; Burger, Christof; Paul, Christian; Wang, Zeng-Li; Kong, Fan-Lin; Welle, Kristian; Jiang, Zhi-Chao; Kabir, Koroush
Abstract : Background: There are many injection therapies for lateral epicondylalgia but there has been no previous comprehensive comparison, based on the Bayesian method. Methods: The MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL) databases were searched for appropriate literature. The outcome measurement was the pain score. Direct comparisons were performed using the pairwise meta-analysis, and network meta-analysis, based on a Bayesian model, was used to calculate the results of all of the potentially possible comparisons and rank probabilities. A sensitivity analysis was performed by excluding low-quality studies. The inconsistency of the model was assessed by means of the node-splitting method. Metaregression was used to assess the relationship between the sample size and the treatment effect. Results: All of the injection treatments showed a trend towards better effects than placebo. Additionally, the peppering technique did not add additional benefits when combined with other treatments. No significant changes were observed by excluding low-quality studies in the sensitivity analysis. No significant inconsistencies were found according to the inconsistency analysis, and metaregression revealed that the sample size was not associated with the treatment effects. Conclusions: Some commonly used injection therapies can be considered treatment candidates for lateral epicondylalgia, such as botulinum toxin, platelet-rich plasma and autologous blood injection, but corticosteroid is not recommended. Hyaluronate injection and prolotherapy might be more effective, but their superiority must be confirmed by more research. The peppering technique is not helpful in injection therapies.